STOIIP validation for a heterogeneous multi-layered reservoir of a mature field using an integrated 3D geo-cellular dynamic model - Mostafa M. Ibrahim; Abdulaziz M. Abdulaziz; Khaled A. Fattah (Egyptian Journal of Petroleum)
The intersecting lobes of bars and channels of Nezzazat group, one of the most complex reservoirs in the Gulf of Suez, concealing underneath a thick salt succession are very difficult to interpret and therefore impose a profound integrated geological and petrophysical study. Such a study encompasses petrophysical characterization of Nezzazat group into seven hydraulic flow units honoring the important developed lithostratigraphic units. To enhance the field development plan, the Big Loop simulation approach is applied to cover all the existing geological and engineering uncertainty. The 3D dynamic simulation model achieved history match to the seven reservoir intervals using RFT pressure data and production logs on layer basis, showing a wide range of permeability and production contribution. The history matched model has proved calculated dynamic STOIIP significantly higher than volumetric STOIIP with additional ±7 MMBO. Such a result encourages drilling a new well to increase the current recovery for the field and achieve a new ultimate recovery. The proposed methodology not only highlights the importance of volumetric STOIIP verifications but also helps understanding the vertical sweep efficiency for different hydraulic flow units that increase the ultimate recovery of the field. Keywords: STOIIP validation, Reservoir uncertainty, Reservoir characterization, Data integration